Wilding the predictive brain. Issue 6 (9th September 2020) - Nave, Kathryn; Deane, George; Miller, Mark; Clark, Andy
Abstract: The Predictive Processing (PP) framework casts the brain as a probabilistic prediction engine that continually generates predictions of the causal structure of the world in order to construct for itself, from the top down, incoming sensory signals. Conceiving of the brain in this way has yielded incredible explanatory power, offering what many believe to be our first glimpse at a unified theory of the mind. In this paper, the picture of the mind brought into view by predictive processing theories is shown to be embodied, deeply affective and nicely poised for cognitive extension. We begin by giving an overview of the main themes of the framework, and situating this approach within embodied cognitive science. We show perception, action, homeostatic regulation and emotion to be underpinned by the very same predictive machinery. We conclude by showing how predictive minds will increasingly be understood as deeply interwoven with, and perhaps extended into, the surrounding social, cultural and technological landscape. This article is categorized under: Philosophy > Foundations of Cognitive Science Psychology > Emotion and Motivation Philosophy > Action Abstract : Our paper "wilds" the popular picture of biological brains as prediction machines. We explore the many ways embodied predictive brains support emotion and action, building minds that extend into surrounding social, cultural and technological landscapes.